Psychographic predictors of intention to use cervical cancer screening services among women attending maternal and child health services in Southern Ethiopia: the theory of planned behavior (TPB) perspective - Fira Abamecha; Atsede Tena; Getachew Kiros (BMC, 2019)
Abstract Background Detection of the premalignant forms cervical cancer through screening in the target age group is one of the effective strategies in the prevention of the disease. Nevertheless, the cervical cancer screening service use remains considerably low in Ethiopia. Indeed; promoting screening behaviors requires understanding the factors influencing women's motivation towards the service. Our study has explored the psycho-graphic factors associated to intention to use cervical cancer screening among women visiting maternal and child health services in Southern Ethiopia, 2017. Methods Institution based cross-sectional study was used employing 422 women's age between 30 and 49 years old. A structured questionnaire was used to collect data on interviewer-administered basis. All assumptions of theory of planned behavior (TPB) were considered to measure intention, attitude, perceived social pressure and perceived ability to control circumstances against cervical cancer screening. Data were analyzed using statistical package for social sciences version 21.0. Multiple linear regression models were conducted to identify factors associated to intention to use cervical cancer screening. P-value less than 5% was considered to indicate significant association. Result Four hundred and two (95%) of the respondents completed the interview. Knowledge of the disease signs, symptoms, risk factors and prevention methods was 162(41.4%). Knowledge about the disease and past screening experience were positively associated with intention to use cervical cancer screening (β = 0.145, 95% CI = [0.047, 0.170]) and (β = 0.098, 95% CI = [0.093, 1.001]) respectively. Further; standardized regression coefficient showed that all dimensions of TPB were positively associated to intention to use the services with perceived behavioral control (β = 0.297, 95% CI = [0.172, 0.343]), perceived social pressure (β = 0.248, 95% CI = [0.131, 0.301]) and attitude towards screening (β = 0.110, CI = [0.018, 0.158]). Conclusion Overall; the intention to use cervical cancer screening was a function of attitude, perceived social pressure and perceived behavioral control confirming the hypothesis of the study. None of the socio-demographic variables were associated to intention. Health behavior change interventions should focus on increasing knowledge and empowering women that enable them to evaluate their control beliefs and develop ability against social norms and circumstances that compete with the use of cervical cancer screening services.